(untitled) (Revista Argentina de Cirugía, 2026)
Background: Centralizing hepatobiliary disease in specialized centers can reduce morbidity and mortality rates and improve long-term outcomes. Objective: The aim of the present study was to describe the clinical and pathological features and surgical outcomes of a series of patients operated on in the Hepatobiliary Surgery and Liver Transplantation Unit of Hospital El Cruce during its first 10 years, as well as the scientific and educational activity of its members. Material and methods: We conducted a descriptive and retrospective study. The information was retrieved from a prospective database. The procedures were classified according to their complexity. An analysis was conducted on liver transplantations (LTs), liver resections and complex biliary procedures, performed from 2013 to 2022. Results: Of 1449 surgical procedures, 832 were high-complexity interventions (58%). A total of 452 LTs were performed, 14 (3%) were combined liver and kidney transplantations; overall transplant survival was 83%, 77% and 75% at 1, 3 and 5 years, respectively. Primary graft dysfunction was observed in 5 cases (1.1%). There were 254 liver resections; 58 cases (23%) were related to benign liver diseases, 155 (61%) to malignancies, and 41 (16%) were associated with living donor transplants. Overall morbidity was 27% and in-hospital mortality was 2%. A total of 106 bilio-digestive bypass procedures were carried out, 53 in patients with bile duct injury. Thirty-day morbidity was 42%, and most cases were minor complications (28%). Other procedures included 17 cephalic pancreaticoduodenectomies and 3 splenectomies and distal pancreatectomies.